A new species of Amyris (Rutaceae) from southern Ecuador - Palacios, Walter A. (Phytotaxa, 2015)
A new species, Amyris karlitae, from southern Ecuador is described, illustrated and contrasted with closely related species. It is characterized by the following combination of characters: glabrous unifoliolate leaves with lamina elliptic, ovate-lanceolate or oblong-elliptic, 6–11 cm long, 4–6 cm wide, with apex acuminate or emarginate; secondary veins in 10–13 pairs, more or less convergent, inconspicuous, branched towards the margin; stamens 8, 4 short alternating with 4 longer. The new species grows in the semi-deciduous forests of southern Ecuador, between 1400 and 1700 m.